Durability of anion exchange membrane water electrolyzers. Issue 6 (5th May 2021) - Li, Dongguo; Motz, Andrew R.; Bae, Chulsung; Fujimoto, Cy; Yang, Gaoqiang; Zhang, Feng-Yuan; Ayers, Katherine E.; Kim, Yu Seung
Abstract : Understanding the durability-limiting factors of anion exchange membrane water electrolyzers operating under pure water-, KOH- and K2 CO3 -fed conditions. Abstract : Interest in the low-cost production of clean hydrogen is growing. Anion exchange membrane water electrolyzers (AEMWEs) are considered one of the most promising sustainable hydrogen production technologies because of their ability to split water using platinum group metal-free catalysts, less expensive anode flow fields, and bipolar plates. Critical to the realization of AEMWEs is understanding the durability-limiting factors that restrict the long-term use of these devices. This article presents both durability-limiting factors and mitigation strategies for AEMWEs under three operation modes, i.e., pure water-fed (no liquid electrolyte), concentrated KOH-fed, and 1 wt% K2 CO3 -fed operating at a differential pressure of 100 psi. We examine extended-term behaviors of AEMWEs at the single-cell level and connect their behavior with the electrochemical, chemical, and mechanical instability of single-cell components. Finally, we discuss the pros and cons of AEMWEs under these operation modes and provide direction for long-lasting AEMWEs with highly efficient hydrogen production capabilities.